Comparative Analysis of Rhizosphere Fungal Communities in Korean Fir Trees - Young Min Ko; Geun-Hye Gang; Dae Ho Jung; Youn-Sig Kwak (Mycobiology)
The Korean fir (Abies koreana), a native coniferous species of Korea, predominantly inhabits the subalpine zone. Recently, this species has experienced a significant population decline, primarily attributed to environmental changes in the subalpine zone driven by global warming. Efforts to prevent the extinction of the Korean fir are underway, with a predominant focus on abiotic factors contributing to its decline. However, there is a notable lack of research on the complex interactions between microbial communities and Korean fir, particularly concerning how these interactions vary with the health status of the trees and their impact on population sustainability. Therefore, this study aimed to elucidate the rhizosphere fungal community structure associated with Korean fir trees in Jirisan National Park. We examined different habitat types, including the rhizospheres of native, cultivated, and dead Korean fir and bulk soil. Our findings revealed that the rhizosphere fungal community in the natural habitat of Korean fir predominantly comprises Agaricomycetes. Furthermore, the fungal community structure was more responsive to habitat type variations than seasonal changes. These findings provide basic information for conserving this endangered species and developing alternative habitats for the Korean fir.